A review of research into stakeholder perspectives on inclusion of students with autism in mainstream schools. Issue 10 (2nd October 2016) - Roberts, Jacqueline; Simpson, Kate
ABSTRACT: Increasing numbers of students with autism are being educated in mainstream schools. However, outcomes for students with autism are poor when compared to typical students and students with other developmental disabilities. In order to better understand facilitators and barriers to success at school for students with autism, research into the attitudes of key stakeholders, educators, parents, people with autism, to inclusion in mainstream schools for students with autism, was reviewed. Key themes emerging included attitudes to inclusion, the characteristics of autism and social communication in particular and interaction with the school environment, and consequent student problem behaviour. Level of knowledge and understanding of school staff emerged as the primary issue with all stakeholders identifying the need for more training. Other support needs identified included the need for structural support, resources and funding. Parents, in particular, identified the need for a collaborative approach to the education process. The findings highlight the need to translate theory into practice to increase capacity in schools to provide effective educational programmes for students with autism.